2016
DOI: 10.1016/j.dnarep.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair enhances convergent transcription-induced cell death at trinucleotide repeats by activating ATR

Abstract: Trinucleotide repeat (TNR) expansion beyond a certain threshold results in some 20 incurable neurodegenerative disorders where disease anticipation positively correlates with repeat length. Long TNRs typically display a bias toward further expansion during germinal transmission from parents to offspring, and then are highly unstable in somatic tissues of affected individuals. Understanding mechanisms of TNR instability will provide insights into disease pathogenesis. Previously, we showed that enhanced converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
(69 reference statements)
2
7
0
Order By: Relevance
“…Transcription induction at both the sense and antisense promoters causes a synergistic increase in cell death at diverse TNRs, triggered by an activated ATR DNA damage response [18, 19, 39]. DNA repair pathways modulate this DNA toxicity effect, with an additional role of mismatch repair (MMR) pathway in regulating ATR activation during convergent transcription [13, 28]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription induction at both the sense and antisense promoters causes a synergistic increase in cell death at diverse TNRs, triggered by an activated ATR DNA damage response [18, 19, 39]. DNA repair pathways modulate this DNA toxicity effect, with an additional role of mismatch repair (MMR) pathway in regulating ATR activation during convergent transcription [13, 28]. …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found that TC-NER and R-loop resolution enzymes lower DNA toxicity of convergent transcription, whereas MMR components increase cell death by activating ATR DNA damage response during convergent transcription [25-28]. Because activated ATR is an important trigger for the Fanconi anemia (FA) pathway to repair interstrand DNA crosslinks [29], we asked whether FA components could also modulate convergent-transcription-induced cell death at CAG repeats.…”
Section: Introductionmentioning
confidence: 99%
“…Typical substrates for the MMR pathway are base mismatches that have arisen during replication and the insertion‐deletion loops (IDLs) within repetitive DNA sequences that have resulted from strand slippage events [Errol C. Friedberg, 2005; Jiricny, ]. MMR is also implicated in a variety of cellular processes including microsatellite stability, meiotic and mitotic recombination, DNA‐damage signaling, apoptosis, class‐switch recombination, somatic hypermutation, and triplet‐repeat expansion [Jiricny, ; Jiricny, ; Chatterjee et al, ]. Germline mutations in the MMR genes result in Lynch syndrome (also known as hereditary nonpolyposis colorectal cancer or HNPCC), which presents as a familial susceptibility to colon and ovarian cancers as well to a number of other cancers [Peltomaki, ].…”
Section: Repair Of Multiple and Bulky Base Damagementioning
confidence: 99%
“…In addition to intergenerational instability, tissue‐specific mosaicism has been observed in polyQ diseases, resulting in cell populations carrying different CAG repeat lengths, within or between tissues . This CAG repeat instability underlies some features of polyQ disorders and may also contribute to their pathogenic mechanism …”
Section: Introductionmentioning
confidence: 99%